Quantitative measurement of ultrasonic pressure field using combination of optical phase contrast and nonlinear acoustic holography methods. (7th June 2018) - Nakamura, Takuya; Iwasaki, Ryosuke; Yoshizawa, Shin; Umemura, Shin-ichiro
Abstract: Ultrasound has been widely used in medicine for both diagnosis and therapeutics. To assure its safety and efficacy, it is necessary to establish a fast and accurate method of measuring an ultrasonic field. Hydrophone scanning, which is a standard method for pressure measurement, requires a long measurement time and may disturb the field. In this study, an optical phase contrast method is combined with an acoustic holography method with nonlinear propagation simulation. The nonaxisymmetric pressure field of pulse ultrasound upstream of the focus was measured by the optical phase contrast method combined with a computed tomography (CT) algorithm, and the entire three-dimensional pressure field was reconstructed by acoustic holography. The result obtained by the proposed method agreed well with that by the hydrophone measurement without absolute pressure calibration and confirmed the markedly reduced required measurement time.